Rare case report on Acitrom induced coagulopathy with seizure disorder - Shakthivel, C. D.; Murugesan, Janane (International Journal of Research in Medical Sciences, 2025)
Acitrom (nicoumalone), a vitamin K antagonist, is widely used for the prevention of thromboembolic disorders. However, its narrow therapeutic index mandates vigilant monitoring to avoid complications like coagulopathy. This case report presents a 59-year-old female with a history of cerebral venous thrombosis, coronary artery disease, and seizures who developed Acitrom-induced coagulopathy. She was admitted with symptoms of headache, vomiting, burning sensation in the lower limbs, and later with bleeding from the gums and oral cavity, melena, and a generalized tonic-clonic seizure. Her past medication included Acitrom, Thyroxin, Atorvastatin, Aspirin, and several other supportive drugs. Investigations revealed deranged coagulation parameters, with INR elevated beyond the therapeutic range. MRI and MRV indicated partial recanalization of cerebral venous sinuses, with no evidence of infarction or hemorrhage. She was managed with intravenous vitamin K, fresh frozen plasma, and antiepileptics including phenytoin and levetiracetam. The offending agent, Acitrom, was discontinued. The patient responded well to treatment and was discharged on antiepileptic and supportive therapy. This case emphasizes the importance of close INR monitoring and patient education to identify early signs of bleeding. Seizure in the context of anticoagulant-induced coagulopathy is rare and requires immediate attention. Interdisciplinary collaboration among neurology, internal medicine, and hematology is critical for optimizing patient outcomes. Early recognition, timely reversal of anticoagulation, and individualized care can significantly reduce morbidity in such complex clinical presentations.